Multilateral policing in Africa: its nature and socio-political impact in Uganda and Sierra Leone, 2003-2005 - Baker, Bruce (UK Data Service, 2006)
Policing in Africa is not a monopoly of government, but is currently undertaken by a number of formal and informal agencies other than the state police. This research project sought to make a detailed and comparative study of all forms of policing in Uganda and Sierra Leone and to establish the current scale and nature of the various forms of policing in the two countries, and why non-state policing is being used. The research documented attitudes to policing in Uganda and Sierra Leone and the degree of multilateral policing in the two countries. In particular it examined who was delivering policing, who was responsible for policing, how many non-state providers of policing existed, what these providers did, and whom they served. Also examined was change in the nature and scope of public policing, whether public police defined their responsibilities differently than in the past, how state and non-state policing agents interact in the field, and whether they plan together, co-ordinate operations, or exchange information. With respect to the commercial security industry, information on how many companies existed was gathered, and how many people they employed. This data collection includes extracts from interviews with key stakeholders, including those who authorise policing, those who provide it and those who use it. A later qualitative study by the same principal investigator, Evaluation of the Effectiveness of Police Local Partnership Boards in Sierra Leone, 2006, is held at the UK Data Archive under SN 5751. Further information about these studies and other research projects on African policing may be found on the principal investigator's Welcome to African Policing web site.